Managing Community on Facing Pandemic COVID-19 in Indonesia - Hikmawan, M. Dian; Mayrudin, Yeby Ma’asan; Ramadhan, Gilang (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
COVID-19 is a concern in today's world, the large number of infected victims followed by a high death rate has made the country take large-scale social restrictions (PSBB). During the pressure of health and economic problems, there is a sense of solidarity among the nation's youth to share and support each other to face the impacts caused by this pandemic. This research focuses on to see how social solidarity is built by many Indonesians, both through social media and on a community basis. Phenomenology is used as the approach used in this study to comprehend a phenomenon comprehensively to know and interpret a phenomenon in-depth, not only as a visible surface. From what we can summarize, strengthening social solidarity appears in various domains and actors, including netizen activism through social media and other channels; the action of the conventional community (Non-Government Organization, Civil Society,) and the role of a traditional and Indigenous Peoples.